Chemical Intervention: New Tools to Dissect Metabolic Signaling. (May 2017) - Ramon, Matthew; Rolland, Filip
Abstract : The metabolic intermediate trehalose-6-P (T6P) has emerged as a key regulator of plant growth and development, but the underlying mechanisms remain largely elusive. A recent publication reported a new chemical intervention strategy, providing a powerful tool to dissect T6P-mediated metabolic signaling.